Social innovation in a local community in Brazil. Issue 3 (27th May 2022) - Castelo, Joelma Leite; Santos, Sandra Maria; da Silva, Clayton Robson Moreira; Aquino, Cíntia Vanessa Monteiro Germano
ABSTRACT: This study investigates the characteristics of social innovation in the community of São Vicente, which benefits from the Community Development and Integration Program, situated in the micro-region of Serra da Meruoca in the Brazilian state of Ceará. To accomplish this, we have conducted a field study along the lines of the technical model used by Tardif and Harrisson (2005), adopting a qualitative approach using semi-structured interviews and direct observations as well as a field diary along with documental analysis. The results make it possible to explore the five analysis categories present in the theoretical model used: (i) transformations; (ii) innovative character; (iii) innovation; (iv) actors and (v) processes. The analyses corroborate the nature of social innovation associated with the development of this community. On the other hand, the processes need to be more professional and formalized, and also should reduce their financial dependence on public bodies.